Conflict, inclusivity, and transformation of the rice value chain in Myanmar - Goeb, Joseph; Minten, Bart; Aung, Nilar; Aung, Zin Wai; Zu, A Myint; Htar, May Thet (International Association of Agricultural Economists, 2024)
In numerous low- and middle-income countries, agricultural value chains (AVC) are undergoing rapid transformation, yet scant evidence exists regarding such changes in fragile and conflict- affected settings, and little is known about inclusivity in this transformation. This study focuses on changes in Myanmar's rice value chain - using unique large-scale primary data - from 2013 to 2022, during an economic boom and subsequent political upheaval and conflict. We document remarkable shifts, including a fourfold increase in rice exports, propelling Myanmar to the world's fifth-largest rice exporter. Concurrently, domestic market conditions improved, and there was modernization in the ‘hidden middle’ of the value chain including increased investments in modern milling equipment and drying methods. At the farm level we note greater adoption of modern inputs (e.g., improved seed) and harvest/post-harvest technologies and increased reliance on modern specialized service providers. The transformation was not everywhere inclusive, and modernization in some areas decelerated due to conflict. Mills and farms in insecure and conflict-affected areas, as well as remote millers and smallholders, participated to a lesser extent, and the gaps widened during the crisis years. The rapid modernization in Myanmar’s rice value chain from 2013 to 2019 highlights the positive impacts of stable governance, infrastructure investment, and liberalization on AVC transformation while the observed variations in modernization inclusivity across different segments of the value chain underscore the complex interplay between governance, conflict, and AVC transformation.